The "China Effect": Changes in international trade patterns as reasons for rising "Anti-Globalism" - Ralph Wrobel (OrdnungsPolitisches Portal (OPO), 2020)
It seems that the "globalization" has failed. Instead, a rising number of people in the Western world prefer old nationalist and protectionist policies. One reason may be the challenge by structural change. Main goal of this paper is to find out if any structural change and any spread of income in the Western World can be traced back to changing trade patterns. Obviously, there is a rising productivity gap between the export-oriented firms and the rest which leads to a rising gap in wages and opportunities for the workers. China is tending towards to trade more human-capital intensively produced goods. That leads to more vertical intra-industry trade with Western countries. While horizontal intra-industry trade brings positive economies of scale and a greater product variety for consumers, vertical intra-industry trade is responsible for more structural change. Especially, unskilled workers in the US and the EU are suffering while highly educated specialists get the gains of the structural change. Therefore, China's rising vertical intra-industry trade is responsible for - at least a part - of the sectoral changes in Western countries and the discrimination of less skilled workers. As a result, low-skilled workers in the Western countries worse off on a sustained basis. This may be one out of a lot of reasons to explain the rise of populism, nationalism and protectionism in current Western politics.
Keywords: 330; International trade; inter-industry and intra-industry trade; economic sectors; China; EU; USA